Implementasi Standar Isi Kurikulum KMA 183 Terhadap Peningkatan Al-Maharah Al-Lughawiyyah dalam Model Pembelajaran Bahasa Arab Komunikatif di Kelas Vii - D. Kadir, Suleman; Yasin, Zohra (Assuthur: Jurnal Pendidikan Bahasa Arab, 2022)
This article discusses the implementation of the standard content of the KMA 183 curriculum for al-maharah al-lughawiyah in the communicative Arabic learning model in grade VII. This article aims to find out how the content of the KMA 183 curriculum towards the direction of improving and mastering the Arabic language with a communicative learning approach in order to achieve the real goal. The main characteristic in the development of KMA 183 is that the curriculum emphasizes mastery of al-maharah al-lughawiyah. That is, in the sense that between theory and practice Arabic learning must be mastered by students. The method used is a descriptive approach in which the results of this problem are taken from data related to curriculum content. The results and studies show that in each translation of KD 3.1 to 3.6 from KI3 and KD 4.1 from KI4 there are verb elements to increase al-mahara al-lughawiyah.